Correlation between Nutritional Status and Severity of Pneumonia in Toddler at Wangaya District Hospital - Susila, I Nyoman Warigardita (WMJ (Warmadewa Medical Journal), 2021)
Pneumonia is still a major health problem in the world, with high morbidity and mortality rates among children under 5 years old, especially in developing countries. In Indonesia, especially Bali, nutritional problem is one of the infection risk factors in children, thus, it is necessary to know the correlation between nutritional status and severity of pneumonia among children under 5 years old at Wangaya District Hospital. This study was based on secondary data. The subjects of this study were paediatric patients diagnosed with pneumonia aged 2 months to 5 years who were treated in Kaswari Room of Wangaya District Hospital from July to December 2019, and were selected by consecutive sampling. The total subjects were 41children with male subjects were more than female (58.5% versus 41.5%). The subjects were mostly in the age groups of 2-10 and 11-20 months old (29.3%); 73.2% of the subjects had good nutrition status, and 73.2% of the cases were non-severe pneumonia. Bivariate analysis between nutritional status and severity of pneumonia obtained p=0.015 and PR of 3.27 (95% CI:1.247-8.590). This study concluded that there was association between nutritional status and severity of pneumonia among children under 5 years old attending Wangaya District Hospital. Keywords: Pneumonia, Nutritional Status, Children under Five Years